Elevated sperm DNA fragmentation is correlated with an increased chromosomal aneuploidy rate of miscarried conceptus in women of advanced age undergoing fresh embryo transfer cycle - Wanting Fu; Wanting Fu; Wanting Fu; Wanting Fu; Qiuying Cui; Qiuying Cui; Qiuying Cui; Qiuying Cui; Zhiqin Bu; Zhiqin Bu; Zhiqin Bu; Zhiqin Bu; et al. (Frontiers in Endocrinology, 2024)
BackgroundMale sperm DNA fragmentation (SDF) may be associated with assisted reproductive technology (ART) outcomes, but the impact of SDF on the occurrence of aneuploid-related miscarriage remains controversial.MethodsGenome-wide single-nucleotide polymorphism-based chromosomal microarray analysis was performed on 495 miscarried chorionic villus samples undergone IVF/ICSI treatment from the Reproductive Medicine Center of the First Affiliated Hospital of Zhengzhou University. SDF was assessed using sperm chromatin structure assay. Patients were divided into four groups according to embryo transfer cycle type and maternal age, and the correlation between SDF and chromosome aberration was analyzed. A receiver operating characteristic (ROC) curve was utilized to find the optimal threshold.ResultsTotal chromosomal aneuploidy rate was 54.95%, and trisomy was the most common abnormality (71.32%). The chromosomally abnormal group had higher SDF than the normal group (11.42% [6.82%, 16.54%] vs. 12.95% [9.61%, 20.58%], P = 0.032). After grouping, elevated SDF was significantly correlated with an increasing chromosome aneuploidy rate only in women of advanced age who underwent fresh embryo transfer (adjusted odds ratio:1.14 [1.00–1.29], adjusted-P = 0.045). The receiver operating characteristic curve showed that SDF can predict the occurrence of chromosomal abnormality of miscarried conceptus in this group ((area under the curve = 0.76 [0.60–0.91], P = 0.005), and 8.5% was the optimum threshold. When SDF was ≥ 8.5%, the risk of such patients increased by 5.76 times (adjusted odds ratio: 6.76 [1.20–37.99], adjusted-P = 0.030).ConclusionFor women of advanced maternal age undergoing fresh embryo transfer, older oocytes fertilized using sperm with high SDF in IVF/ICSI treatment might increase the risk of chromosomal abnormality in miscarried conceptus.